Aged polystyrene nanoplastics and bisphenol A co-exposure impair mitochondrial respiration in juvenile horseshoe crab Tachypleus tridentatus - Kangping Jiao; Youji Wang; Yuntian Shi; Moslem Sharifinia; Nisha Singh; Khor Waiho; Hanafiah Fazhan; Jae-Seong Lee; James Kar-Hei Fang; Kit Yue Kwan; Marta Sendra; Menghong Hu (Marine Pollution Bulletin, 2026)

Cover Image - Faisal Ahmad Lodhi; Fahim Ullah Khan; Aabid Ullah Khan; Jae‐Seong Lee; Muhammad Abbas; Hanafiah Fazhan; Khor Waiho; Menghong Hu; Youji Wang (Reviews in Aquaculture, 2026)
The cover image is based on the article Multi‐Stressor Responses in Marine Bivalves: Integrating Climate Change, Pollutants, and Microbiome Shifts for Aquaculture Resilience by Faisal Ahmad Lodhi et al., https://doi.org/10.1111/raq.70169 . image

Multi‐Stressor Responses in Marine Bivalves: Integrating Climate Change, Pollutants, and Microbiome Shifts for Aquaculture Resilience - Faisal Ahmad Lodhi; Fahim Ullah Khan; Aabid Ullah Khan; Jae‐Seong Lee; Muhammad Abbas; Hanafiah Fazhan; Khor Waiho; Menghong Hu; Youji Wang (Reviews in Aquaculture, 2026)
Marine bivalves play pivotal ecological and economic roles but are increasingly challenged by multiple environmental stressors. Although there is extensive research on the effects of individual stressors, a comprehensive review is needed to synthesize current evidence and clarify how multiple interacting stressors collectively affect the physiology and resilience of marine bivalves. This review integrates evidence from 2010 to 2025, encompassing 178 peer‐reviewed studies emphasizing the combined and interactive impacts of climate change drivers (warming, hypoxia, salinity, and ocean acidification), pollutants (heavy metals, persistent organic pollutants, endocrine‐disrupting chemicals, antibiotics, nanoparticles, microplastics), and microbiome shifts on future aquaculture resilience. Literature was systematically retrieved from Web of Science, Scopus, PubMed, and Google Scholar in accordance with PRISMA 2020 guidelines. Bibliometric mapping (VOSviewer 1.6.20) revealed a rapid growth in research after 2018, characterized by studies on Mytilus , Crassostrea , and Ruditapes . A systematic evaluation of recent evidence was conducted, combining data from physiological, molecular, and microbial studies, with particular attention to implications for aquaculture. The analysis reveals that stressors rarely act alone. Instead, their cumulative and interactive effects cause oxidative stress, disrupted energy allocation, destabilized host‐microbe relationships, lowered tolerance thresholds, and other eco‐physiological consequences. These results highlight the vulnerability of bivalve populations to rapid coastal urbanization, declining water quality, and sediment contamination. The review concludes that resilience can be enhanced through selective breeding for stress‐tolerant genotypes, integrated monitoring of pollutants and microbial indicators, and multi‐omics approaches to guide adaptive aquaculture management.

Understanding the Relationship Between Rhizocephalans and Their Hosts From the Lens of Omics: Implications Towards Crustacean Aquaculture - Yang Yu; Youji Wang; Kianann Tan; Menghong Hu; Nor Afiqah‐Aleng; Melissa Beata Martin; Lihan Zhang; Hanafiah Fazhan; Khor Waiho (Reviews in Aquaculture, 2026)
The continuous development of high‐throughput sequencing technologies has revolutionised the field of food production and agriculture, including aquaculture. In addition to fish, crustaceans play a crucial role in supporting coastal economies and serve as a valuable source of high‐quality protein worldwide. Therefore, the prevention and treatment of diseases, especially in commercially valuable crustaceans, are of paramount importance. Among the various parasites affecting crustaceans, rhizocephalan parasites have recently gained widespread attention due to their severe effects on hosts, including moult inhibition, parasitic castration and feminisation, reduction in metabolism and survival, and behavioural changes. This review employs a systematic literature review approach to summarise progress in omics research regarding host‐rhizocephalan interactions. The final dataset comprised 12 articles from four rhizocephalan families (Thompsoniidae, Sacculinidae, Polyascidae, and Peltogasterellidae). The review further discusses advances in omics research across five main functional categories: growth and moulting, metabolism, sex differentiation and reproduction, immunity and disease, and population genetics and evolution. Differentially expressed genes, proteins, metabolites, and pathways identified in rhizocephalan‐related omics studies serve as a valuable molecular database to understand host responses and rhizocephalan infection strategies. Key factors, including juvenile hormone esterase ( JHE ), thioredoxin, Kazal‐type protease inhibitor ( KPI ), heat shock proteins ( HSP70/HSP90 ), and cathepsins , are multi‐functionally involved in host‐rhizocephalan interactions. However, knowledge gaps persist, hindered by limitations in diagnostic tools and data integration. Future directions, such as single‐cell sequencing (scRNA‐seq), multi‐omics approaches, and protein–protein interaction (PPI) networks, offer promise for advancing our understanding of host–parasite dynamics, providing insights for rhizocephalan parasitology control in sustainable crustacean aquaculture health.

Current Advances in the Black Tiger Shrimp Penaeus monodon Culture: A Review - Khor Waiho; Yang Ling; Mhd Ikhwanuddin; Alexander Chong Shu‐Chien; Nor Afiqah‐Aleng; Youji Wang; Menghong Hu; Honjung Liew; Nor Azman Kasan; Jia Hui Peh; Hanafiah Fazhan (Reviews in Aquaculture, 2025)
The increasing high‐end market demand for the black tiger shrimp Penaeus monodon has brought tremendous industry opportunities. Although the industry has tried its best to increase production, according to the report data from the Food and Agriculture Organization (FAO), annual global production has shown no significant upward trend over the past decade. Besides that, newly implemented policies such as seafood safety and food security negatively impacted the industry and reduced production. However, P. monodon cultivation is still promising due to its larger body size and higher market acceptance as a premium product. Over the years, numerous studies have been conducted to increase the production of P. monodon by optimizing its culture conditions, implementing new culture system, increasing disease resistance to disease such as WSSV, AHPND, WFD, implementation of pre‐ and probiotics in feed, and selective breeding programs to increase genetic diversity and population of P. monodon broodstock. This review provides an overview of the current advances in P. monodon broodstock cultivation, thereby providing an essential baseline for P. monodon aquaculture. Areas needing urgent research focus are also highlighted. Future research should take great strides and take into account the impact of future climate change scenario during P. monodon culture and optimization, and increase biosecurity measures to prevent its introduction as an alien species in wild settings.

Interspecific hybridization of decapod crustacean species with commercial interest—A review - Muhammad Nur Syafaat; Muyassar H. Abualreesh; Norhafiza Ilyana Yatim; Hanafiah Fazhan; Khor Waiho; Hongyu Ma; Victor Tosin Okomoda; Mhd Ikhwanuddin (Reviews in Aquaculture, 2024)
Interspecies hybridization has been widely used in the development of aquaculture in fish species but there is not much impact in crustacean species. Several species of crustaceans that have been successfully crossed still have low hatching rates and the hybrids obtained have not met expectations. This review tries to summarize and analyse interspecific hybridization of cultured crustacean species (shrimps, lobsters, crayfish and crabs) and its potential for development of crustacean aquaculture production. The success of cross‐breeding on several species of shrimp and lobster has been supported by artificial insemination technology. In crabs, artificial insemination cannot be applied and cross‐breeding still relies on natural mating with an unstable success rate. In addition to cross‐breeding in captivity, cross‐breeding of crustacean species (shrimp, lobster, crayfish and crab) in nature has also been found. Interbreeding of crustacean species in nature cannot always be distinguished morphologically, hybrids between them can be known with certainty after carrying out molecular analysis. Even though the level of reproductive performance in cross‐breeding of shrimp, lobster, crayfish and crab species is still low, cross‐breeding efforts must be continued to obtain more information so that it can later be mapped which species have the potential to develop hybrids for cultivation. Furthermore, growth, reproductive performance, monosex hybridity and disease resistance are all hybrid parameters that must be evaluated.

Transcriptomics in advancing portunid aquaculture: A systematic review - Khor Waiho; Mhd Ikhwanuddin; Nor Afiqah‐Aleng; Alexander Chong Shu‐Chien; Youji Wang; Hongyu Ma; Hanafiah Fazhan (Reviews in Aquaculture, 2022)
The rapid advancement of next‐generation sequencing technologies has promoted the use of transcriptomics in non‐model organisms, including species in the aquaculture sector. Compared to that of other crustacean species, portunid crab aquaculture is impeded by the insufficient knowledge of their biological and physiological processes. This systematic review summarised the advances in transcriptomics in cultured portunid crabs using a systematic literature review methodology. The filtered transcriptome dataset comprised 66 articles from four genera: Scylla , Portunus , Callinectes and Charybdis . At the species level, Scylla paramamosain and Portunus trituberculatus were the two most studied species, highlighting their importance in the aquaculture sector. The affordable cost of RNA sequencing (RNA‐Seq) led to an increase in transcriptome‐related research in portunid crabs and made available a huge repertoire of differentially expressed genes (DEGs) and single nucleotide polymorphisms (SNPs). We further discussed the transcriptomic advances based on six main functional categories, that is, ‘growth and moulting’, ‘gonadal development and reproduction’, ‘nutrition metabolism’, ‘disease and immunity’, ‘toxicology and stress’ and ‘general transcriptomic profiling’. In general, transcriptomic studies of portunid crabs, specifically the DEGs and pathways allow an in‐depth understanding of the biological and physiological processes involved at different growth stages or under various conditions based on the difference in gene transcriptional activity. SNPs obtained from the transcriptome data are useful in many genetic improvement‐related downstream applications, including the construction of genetic linkage maps and as population genetic markers. Future directions, such as hybrid approaches of long‐read and common RNA‐Seq, and the incorporation of other omics were also discussed.

Recent development in ecdysone receptor of crustaceans: current knowledge and future applications in crustacean aquaculture - Muhammad‐Redha Abdullah‐Zawawi; Nor Afiqah‐Aleng; Mhd Ikhwanuddin; Yeong Yik Sung; Siriporn Tola; Hanafiah Fazhan; Khor Waiho (Reviews in Aquaculture, 2021)
Ecdysone receptor (EcR) is the primary regulator of the ecdysteroid signalling pathway, a critical pathway that directly links to moulting. In addition, EcR also regulates growth, development, reproduction and regeneration in crustaceans. However, there remains a huge gap of knowledge between the detailed structure and functional role(s) of crustacean EcR compared to that of insects. Motif and phylogenetic analyses of publicly available crustacean EcR proteins revealed the evolutionary relationship of EcR in this subphylum and highlighted its conserved characteristics among crustaceans. The role of EcR in the regulation of essential physiological processes in crustaceans including moulting, chitin synthesis, general growth and development, gonadal and maturation, and limb regeneration was discussed based on the available literature. This essential moult‐related nuclear receptor could serve as a useful molecular indicator of moulting and gonadal maturation, as a potential target for pesticide production against parasitic crustacean species in the aquaculture industry, as well as valuable bioindicators of environmental stressors.

Protein–protein interaction network: an emerging tool for understanding fish disease in aquaculture - Khor Waiho; Nor Afiqah‐Aleng; Mat Taib Mimi Iryani; Hanafiah Fazhan (Reviews in Aquaculture, 2021)
Protein–protein interactions (PPIs) play integral roles in a wide range of biological processes that regulate the overall growth, development, physiology and disease in living organisms. With the advancement of high‐throughput sequencing technologies, increasing numbers of PPI networks are being predicted and annotated, and these contribute greatly towards the understanding of pathogenesis and the discovery of novel drug targets for the treatment of diseases. The use of this tool is gaining popularity in the identification, understanding and treatment of diseases in humans and plants. Due to the importance of aquaculture in tackling the global food crisis by producing cheap and high‐quality protein source, the maintenance of the overall health status of aquaculture species is essential. With the increasing omics data on aquaculture species, the PPI network is an emerging tool for fish health maintenance. In this review, we first introduce the concept of PPI network, how they are discovered and their general application. Then, the current status of aquaculture and disease in aquaculture are discussed. The different applications of PPI network in aquaculture fish disease management such as biomarker identification, mechanism prediction, understanding of host–pathogen interaction, understanding of pathogen co‐infection interaction, and potential development of vaccines and treatments are subsequently highlighted. It is hoped that this emerging tool – PPI network – would deepen our understanding of the pathogenesis of various diseases and hasten the prevention and treatment processes in aquaculture species.